Visceral fat is associated with the racial differences in liver fat between black and white adolescent boys with obesity - Lee, SoJung (Pediatr Diabetes, 2017)
OBJECTIVE: We examined whether racial differences in liver fat is associated with the differences in abdominal fat distribution or cardiorespiratory fitness (CRF). METHODS: Participants included 57 black and white obese boys (12–18 yrs). Total and abdominal fat was measured by DEXA and MRI, respectively. CRF was measured using a maximal graded treadmill test with the use of standard open-circuit spirometry techniques until volitional fatigue. Liver fat was measured using a 3T proton magnetic resonance spectroscopy. Fatty liver was defined as having liver fat ≥5%. RESULTS: In the sample, 16.1% of black boys and 30.8% of white boys had fatty liver. Liver fat was associated (P≤0.05) with BMI percentile (r=0.28), total fat (r=0.31), waist circumference (r=0.38), visceral fat (r=0.62), ASAT (r=0.30), and CRF (r= −0.27) adjusting for age and race. White boys had greater liver fat than black boys with adjustment for age and differences in BMI percentile or CRF, but not with waist circumference or visceral fat (P>0.05). In a model with age, ethnicity, total body fat, fat free mass, visceral fat, abdominal subcutaneous fat and CRF, visceral fat was the only factor to be independently associated with increased odds of having fatty liver (OR= 1.12, 95% CI: 1.04–1.21, P=0.003). CONCLUSION: The racial disparities in liver fat between obese black versus white adolescents are explained, in part, by differences in visceral fat.